Quantum dot material for coating or ink-jet printing and preparation method and application thereof

Through the method of surface modification of quantum dot ligands and dispersing ligands in ink, the problems of poor aggregation and film formation in quantum dot inkjet printing are solved, and more stable quantum dot materials and more uniform pixel dots are achieved.

CN119708923APending Publication Date: 2025-03-28WUXI UTMOST LIGHT TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311263780.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the existing quantum dot inkjet printing technology, quantum dots have poor compatibility with ink and are prone to agglomeration, resulting in blocking the nozzle, poor film formation, uneven pixel dots, and coffee ring phenomenon, affecting application.

Method used

The quantum dots are modified by the surface of the quantum dot ligand, making them strongly anchored to the quantum dot ligand, improving the stability of the quantum dots, and the other end of the quantum dot ligand is acrylate functional group or olefin functional group, so that it can be freely dispersed in the ink, avoiding agglomeration, and participating in the UV curing fixed environment.

Benefits of technology

It effectively solves the agglomeration problem of quantum dot ink during coating or inkjet printing, improves film formation and pixel dot uniformity, and enhances the stability of quantum dot materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708923A_ABST
    Figure CN119708923A_ABST
Patent Text Reader

Abstract

The invention provides a quantum dot material for coating or ink-jet printing as well as a preparation method and application of the quantum dot material. The quantum dot material comprises a quantum dot and a quantum dot ligand coordinated with the quantum dot, one end of the quantum dot ligand is coordinated with the quantum dot, and the other end of the quantum dot ligand is an acrylate functional group or an olefin functional group; the acrylate functional group or the olefin functional group can be freely dispersed in an organic solvent or bonded with an organic material. The quantum dots are subjected to surface modification by adopting the quantum dot ligands, so that one ends of the quantum dot ligands are coordinated with the quantum dots, the strong anchoring effect can improve the stability of the quantum dots in the manufacturing process, the other ends of the quantum dot ligands can be well dispersed in the ink, and the problems encountered in the coating or ink-jet printing process of the quantum dot ink are effectively solved; and the quantum dot ligand participates in UV curing, so that the environment of the quantum dot can be further fixed, and the stability of the quantum dot material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of display technology, and in particular relates to a quantum dot material for coating or inkjet printing, and a preparation method and application thereof. Background Art

[0002] Quantum dots are excellent display materials for the next generation due to their wide absorption, narrow emission, high color purity, and high fluorescence efficiency. In order to further improve the color gamut of the display while reducing energy consumption, extensive research and industrial development of quantum dot display technology is being conducted. Quantum dot inkjet printing technology has low power consumption, high precision, no need for masks (saving printing materials), and can achieve high-precision pixels. It is a key technology from liquid crystal displays (LCDs) to mini-LEDs and micro-LEDs.

[0003] At present, quantum dot coating or inkjet printing technology generally synthesizes quantum dots (II-VI group cadmium selenide, III-V group indium phosphide or perovskite, etc.), then purifies the quantum dots, and then disperses the quantum dots in UV ink for coating or inkjet printing. For example, CN107474632A discloses a method of dispersing perovskite quantum dots in a solvent with a boiling point greater than 200°C, and then adding a viscosity regulator and a surface tension regulator to finally prepare a perovskite ink for inkjet printing. CN109321038A discloses a method of dispersing II-VI group cadmium selenide and III-V group indium phosphide in a low-polarity or non-polar single solvent or mixed solvent to suppress the coffee ring phenomenon of ink film formation.

[0004] It can be seen that the current quantum dot inkjet printing technology is to simply disperse quantum dots in ink. During the storage, transportation, coating or printing process, due to the poor compatibility between quantum dots and ink, it is easy to agglomerate, and even the perovskite quantum dots have the phenomenon of further growth, thereby clogging the nozzle, slowing down the printing speed and even causing nozzle damage. In addition, poor dispersion can easily lead to the agglomeration of quantum dots in pixels, so that film formation cannot be achieved or the pixels are uneven. In addition, the ink components currently matched with quantum dots are relatively complex. Due to the large differences in surface tension and volatility between the components, the pixels of inkjet printing are prone to coffee ring phenomenon, which seriously affects the application of quantum dot inkjet printing technology and also affects the uniformity of coating. In particular, there is no interaction between quantum dots and ink. The quantum dots in the solidified pixels are physically wrapped by organic molecules. During the application process, quantum dots are prone to agglomeration, decomposition, regrowth and other undesirable changes under the influence of factors such as light, heat, water, and oxygen.

[0005] Therefore, designing a new type of quantum dot material for coating or inkjet printing that can avoid the above problems and meet the requirements of coating or inkjet printing is one of the research directions that urgently needs to be studied. Summary of the invention

[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a quantum dot material for coating or inkjet printing, and its preparation method and application. The present invention uses quantum dot ligands to modify the quantum dots on the surface, so that one end of the quantum dot ligand is anchored to the quantum dot ligand. This strong anchoring effect can effectively avoid the negative changes such as agglomeration, decomposition, and ion exchange of quantum dot materials during the application process and under the influence of factors such as light, heat, water, and oxygen, thereby improving the stability of quantum dots in the process. The other end of the quantum dot ligand can be well dispersed in the ink, effectively solving the problems of agglomeration of quantum dot ink during coating or inkjet printing, resulting in nozzle blockage, poor film formation, and uneven pixel points themselves. In addition, the quantum dot ligand participates in UV curing, which can further fix the environment of the quantum dots, which is beneficial to improving the stability of the quantum dot material.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a quantum dot material for coating or inkjet printing, the quantum dot material comprising quantum dots, and quantum dot ligands coordinated with the quantum dots, one end of the quantum dot ligands coordinated with the quantum dots, and the other end of the quantum dot ligands being an acrylate functional group or an olefin functional group;

[0009] The acrylate functional group or the olefin functional group can be freely dispersed in an organic solvent or bonded to an organic material.

[0010] The present invention uses quantum dot ligands to modify the quantum dots on the surface, so that one end of the quantum dot ligand is coordinated with the quantum dot ligand, for example, SO3 / PO4 / S groups are coordinated with Pb ions, and N of the quaternary ammonium salt is coordinated with the + With Br - Coordination, this strong anchoring effect can effectively avoid negative changes such as aggregation, decomposition, ion exchange, etc. of quantum dot materials during the application process and under the influence of factors such as light, heat, water, and oxygen, thereby improving the stability of quantum dots in the process. The other end of the quantum dot ligand can be well dispersed in organic solvents or bonded with organic materials, which can effectively solve the problems of subsequent quantum dot inks agglomerating during coating or inkjet printing, resulting in nozzle clogging, poor film formation, and uneven pixel points themselves. In addition, the quantum dot ligands participate in UV curing, which can further fix the environment of the quantum dots, which is beneficial to improving the stability of the quantum dot materials.

[0011] It should be noted that the acrylate functional group or olefin functional group is compatible with organic solvents, which can make the quantum dots coordinated with the quantum dot ligands well dispersed, preventing the subsequent quantum dot ink from agglomerating during coating or inkjet printing. In addition, the acrylate functional group or olefin functional group of the quantum dot ligand can participate in the polymerization of the monomer in the UV glue, thereby further fixing the environment of the quantum dots and encapsulating the quantum separator in the organic polymer, which is beneficial to improving the stability of the quantum dot material.

[0012] As a preferred technical solution of the present invention, the general chemical formula of the quantum dot ligand includes:

[0013] X1-R2-SO3 / PO4 / S-R1, X2-R2-N(-R1)-R4-SO3 / PO4 / S-R3 and X3-R2-(R3-)N + At least one of (-R4)-R1-SO3 / PO4 / COO-R3, wherein X1, X2, X3 or X4 is independently an acrylate functional group or an olefin functional group, preferably an acrylate functional group.

[0014] It should be noted that "independently" means that X1 can select an acrylate functional group or an olefin functional group, X2 can select an acrylate functional group or an olefin functional group, X3 can select an acrylate functional group or an olefin functional group, and X4 can select an acrylate functional group or an olefin functional group, and the selection of the four does not interfere with each other, and the same or different ones can be selected. The "independently" in the present invention is the same.

[0015] It should be noted that X1-R2-SO3 / PO4 / S-R1 refers to any one of X1-R2-SO3-R1, X1-R2-PO4-R1 or X1-R2-S-R1, X2-R2-N(-R1)-R4-SO3 / PO4 / S-R3 refers to any one of X2-R2-N(-R1)-R4-SO3-R3, X2-R2-N(-R1)-R4-PO4-R3 or X2-R2-N(-R1)-R4-S-R3, X3-R2-(R3-)N + (-R4)-R1-SO3 / PO4 / COO-R3 refers to X3-R2-(R3-)N + (-R4)-R1-SO3-R3, X3-R2-(R3-)N + (-R4)-R1-PO4-R3 or X3-R2-(R3-)N + Any one of (-R4)-R1-COO-R3.

[0016] Preferably, R1, R2, R3 or R4 independently includes any one of a hydrogen group, an alkyl group, an aromatic hydrocarbon group or an ester group, preferably an alkyl group.

[0017] As a preferred technical solution of the present invention, the quantum dot ligand includes 3-[bis[2-(methacryloyloxy)ethyl](methyl)amino]propane-1-sulfonate, 1-(3-sulfopropyl)-2-vinylpyridine hydroxide inner salt, 3-[[2-(acryloyloxy)ethyl]dimethylammonium]propane-1-sulfonate, oleyl betaine, (E)-4-fluorophenethyl 3-(3-hydroxy-4-(methylsulfonyl)phenyl)acrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-[(3-acrylamidopropyl)dimethylammonium]propane-1-sulfonate, 3-methylacrylate sulfopropyl ester, 11-phosphonic acid undecyl acrylate and at least one of lecithin.

[0018] As a preferred technical solution of the present invention, the quantum dots include at least one of perovskite quantum dots, II-VI group cadmium selenide quantum dots and III-V group indium phosphide quantum dots.

[0019] It should be noted that the present invention does not limit the specific type of perovskite quantum dots. For example, they may be FAPbBr3 perovskite quantum dots or CsPbBr3 perovskite quantum dots.

[0020] In a second aspect, the present invention provides a method for preparing a quantum dot material for coating or inkjet printing as described in the first aspect, the preparation method comprising the following steps:

[0021] The quantum dot precursor solution and the quantum dot ligand are mixed, and then heat-treated, and then the precursor material obtained by the heat treatment is mixed with an organic solvent, and a reaction is performed to obtain the quantum dot material for coating or inkjet printing; or,

[0022] The quantum dot solution and the quantum dot ligand solution are mixed and subjected to a secondary reaction to obtain the quantum dot material for coating or inkjet printing.

[0023] As a preferred technical solution of the present invention, the organic solvent includes dichloromethane;

[0024] Preferably, the temperature of the primary reaction is room temperature.

[0025] It should be noted that the present invention does not limit the specific temperature of the room temperature. For example, it can be 20°C, 25°C or 30°C.

[0026] Preferably, the time of the primary reaction is 3-8 s, for example, 3 s, 4 s, 5 s, 6 s, 7 s or 8 s.

[0027] As a preferred technical solution of the present invention, after the one reaction, the molar ratio of the obtained quantum dots to the quantum dot ligands is 1:(0.2-1), for example, it can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, etc., preferably 1:(0.5-1).

[0028] In the present invention, if the molar ratio of quantum dots and quantum dot ligands is too small, that is, the content of quantum dot ligands is too large, the ligands will inhibit the growth of quantum dots, resulting in small particle size or even failure to generate; if the molar ratio of quantum dots and quantum dot ligands is too large, that is, the content of quantum dot ligands is too small, the quantum dots will grow too fast and the particle size will be too large, the optical properties will be poor, and even agglomeration will fail.

[0029] Preferably, the mass ratio of the solute in the quantum dot solution to the solute in the quantum dot ligand solution is 1:(0.2-1), for example, it can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, etc., preferably 1:(0.5-1).

[0030] Preferably, the heat treatment temperature is 70-120°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, etc. If the temperature is lower than 70°C, the ligand cannot be completely dissolved, and if the temperature is higher than 120°C, the temperature is too high, which may cause organic substances such as formamidine to volatilize.

[0031] It should be noted that the present invention does not limit the time of heat treatment, as long as the solid is completely dissolved.

[0032] Preferably, the blending time is 20-40 min, for example, 20 min, 25 min, 30 min, 35 min or 40 min, etc. If the blending time is less than 20 min, the ligand cannot be completely dissolved, and if the stirring time is more than 40 min, the preparation time is prolonged.

[0033] In a third aspect, the present invention provides a quantum dot ink for coating or inkjet printing, wherein the quantum dot ink comprises the quantum dot material as described in the first aspect.

[0034] As a preferred technical solution of the present invention, when the quantum dot ink is used for coating, the coating viscosity ranges from 100-1500cp, for example, it can be 100cp, 300cp, 500cp, 700cp, 900cp, 1100cp, 1300cp or 1500cp, etc., and the surface tension ranges from 100-1000dyne / cm, for example, it can be 100dyne / cm, 200dyne / cm, 400dyne / cm, 600dyne / cm, 800dyne / cm or 1000dyne / cm, etc.

[0035] It should be noted that when the quantum dot ink is applied, the viscosity of the quantum dot ink applied can be effectively adjusted by adjusting the ratio of oligomer (high viscosity) to monomer / diluent (low viscosity).

[0036] Preferably, when the quantum dot ink is used for inkjet printing, the viscosity range is 0.5-30cp, for example, it can be 0.5cp, 1cp, 5cp, 10cp, 15cp, 20cp, 25cp or 30cp, and the surface tension range is 15-55dyne / cm, for example, it can be 15dyne / cm, 20dyne / cm, 25dyne / cm, 30dyne / cm, 35dyne / cm, 40dyne / cm, 45dyne / cm, 50dyne / cm or 55dyne / cm, etc.

[0037] In a fourth aspect, the present invention provides a method for preparing the quantum dot ink as described in the third aspect, the preparation method comprising the following steps:

[0038] The quantum dot material, UV glue, initiator and organic solvent are mixed to obtain the quantum dot ink.

[0039] As a preferred technical solution of the present invention, the mass of the quantum dot material accounts for 5-50wt.% of the mass of the quantum dot ink, for example, it can be 5wt.%, 10wt.%, 15wt.%, 20wt.%, 25wt.%, 30wt.%, 35wt.%, 40wt.%, 45wt.% or 50wt.%, etc., preferably 15-30wt.%.

[0040] In the present invention, if the mass content of the quantum dot material is too low, multiple printing / coatings are required to achieve a color conversion layer / pixel point that meets optical requirements; if the mass content of the quantum dot material is too high, the ink viscosity will be too high, affecting the printing effect.

[0041] Preferably, the UV glue comprises a monomer.

[0042] Preferably, the monomer includes at least one of polyethylene glycol (200) dimethacrylate, isooctyl acrylate, isodecyl acrylate, polyethylene glycol (400) dimethacrylate, polyethylene glycol (600) dimethacrylate, tricyclodecane dimethanol methacrylate, trimethylolpropane formal acrylate, triethylene glycol diacrylate glycidyl methacrylate, polypropylene glycol (400) dimethacrylate, isobornyl methacrylate, phenoxyethyl acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate and 1,4-butanediol diacrylate.

[0043] Preferably, the UV glue further comprises an oligomer.

[0044] Preferably, the oligomer includes at least one of aliphatic urethane acrylate, aromatic urethane acrylate, epoxy acrylate and fluorocarbon resin.

[0045] Preferably, the initiator includes at least one of 1173 initiator, 4265 initiator, 2959 initiator, TPO-L initiator and TPO initiator.

[0046] It should be noted that the chemical name of initiator 1173 is 2-hydroxy-2-methyl-1-phenyl-1-propanone, the chemical name of initiator 4265 is a composite initiator of 50% 2-hydroxy-2-methyl-1-phenyl-1-propanone and 50% 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, the chemical name of initiator 2959 is 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, the chemical name of initiator TPO-L is ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and the chemical name of initiator TPO is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0047] It should be noted that the initiator used in the present invention can be dissolved in ink, has no damage to quantum dots, and can quickly initiate curing.

[0048] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] The present invention uses quantum dot ligands to modify the quantum dots on the surface, so that one end of the quantum dot ligand is anchored to the quantum dot ligand. This strong anchoring effect can effectively avoid negative changes such as aggregation, decomposition, ion exchange, etc. of the quantum dot material during the application process and under the influence of factors such as light, heat, water, and oxygen, thereby improving the stability of the quantum dots in the process. The other end of the quantum dot ligand can be well dispersed in the ink, effectively solving the problems of nozzle clogging, poor film forming properties, and uneven pixel points caused by the aggregation of quantum dot ink during coating or inkjet printing. In addition, the quantum dot ligand participates in UV curing, which can further fix the environment of the quantum dots, which is beneficial to improving the stability of the quantum dot material. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a fluorescence spectrum of the quantum dot material prepared in Example 1 of the present invention.

[0052] Figure 2 This is a fluorescence spectrum of the quantum dot material prepared in Example 2 of the present invention.

[0053] Figure 3 This is a fluorescence spectrum of the quantum dot material prepared in Example 3 of the present invention.

[0054] Figure 4 This is a fluorescence spectrum of the quantum dot material prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] Example 1

[0057] This embodiment provides a quantum dot material for coating or inkjet printing, the quantum dot material comprising FAPbBr3 perovskite quantum dots, and quantum dot ligands coordinated with the quantum dots, one end of the quantum dot ligands coordinated with the quantum dots, and the other end of the quantum dot ligands is an acrylate functional group;

[0058] The quantum dot ligand is 3-[bis[2-(methacryloyloxy)ethyl](methyl)amino]propane-1-sulfonate.

[0059] This embodiment also provides a method for preparing the above quantum dot material, the preparation method comprising the following steps:

[0060] 0.1124 g FABr and 0.3670 g PbBr2 were added to 10 mL of DMF and stirred to dissolve, and then 0.1887 g 3-[bis[2-(methacryloyloxy)ethyl](methyl)amino]propane-1-sulfonate was added, and the mixture was heated to 90° C. and stirred until the solid was completely dissolved, and then the obtained precursor material was inverted into 300 mL of dichloromethane organic solvent, and the mixture was stirred openly at room temperature of 25° C. for 5 seconds to react once, thereby obtaining the quantum dot material;

[0061] Among them, the molar ratio of the generated FAPbBr3 perovskite quantum dots and 3-[bis[2-(methacryloyloxy)ethyl](methyl)amino]propane-1-sulfonate is 1:0.55.

[0062] This embodiment also provides a method for preparing quantum dot ink, the preparation method comprising the following steps:

[0063] The prepared quantum dot material was centrifuged and stirred at 6000 rpm for 3 min, and the obtained precipitate was dispersed in 2 g of polyethylene glycol (200) dimethacrylate, and then centrifuged and stirred at 6000 rpm for 3 min, and the supernatant was taken and then mixed with 20 μL of 1173 initiator to obtain quantum dot ink;

[0064] The mass of the quantum dot material accounts for 18 wt.% of the mass of the quantum dot ink.

[0065] This embodiment also provides an application of the quantum dot ink. When the quantum dot ink is applied to inkjet printing, the viscosity is 20 cp and the surface tension is 40 dyne / cm.

[0066] Example 2

[0067] This embodiment provides a quantum dot material for coating or inkjet printing, the quantum dot material comprising CsPbBr3 perovskite quantum dots, and quantum dot ligands coordinated with the quantum dots, one end of the quantum dot ligands coordinated with the quantum dots, and the other end of the quantum dot ligands is an acrylate functional group;

[0068] The quantum dot ligand is 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt.

[0069] This embodiment also provides a method for preparing the above quantum dot material, the preparation method comprising the following steps:

[0070] 0.1915 g of CsBr and 0.3670 g of PbBr2 were added to 10 mL of DMF and stirred to dissolve, and then 0.1396 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt was added, and the mixture was heated to 90° C. and stirred until the solid was completely dissolved, and then the obtained precursor material was inverted into 300 mL of dichloromethane organic solvent, and the mixture was stirred openly at room temperature of 25° C. for 5 seconds to react once, thereby obtaining the quantum dot material;

[0071] Among them, the molar ratio of the generated CsPbBr3 perovskite quantum dots and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt is 1:0.55.

[0072] This embodiment also provides a method for preparing quantum dot ink, the preparation method comprising the following steps:

[0073] The quantum dot material prepared above was centrifuged and stirred at 6000 rpm for 3 min, and the obtained precipitate was dispersed in 10 mL of toluene, and then centrifuged and stirred at 6000 rpm for 3 min, the supernatant was taken, 2 g of isooctyl acrylate was added, and vacuum was drawn until there were no bubbles, and then 0.5 g of tricyclodecane dimethanol methacrylate and 20 μL of 1173 initiator were added thereto to mix, and a quantum dot ink was obtained;

[0074] The mass of the quantum dot material accounts for 17 wt.% of the mass of the quantum dot ink.

[0075] This embodiment also provides an application of the quantum dot ink. When the quantum dot ink is applied to inkjet printing, the viscosity is 25 cp and the surface tension ranges from 55 dyne / cm.

[0076] Example 3

[0077] This embodiment provides a quantum dot material for coating or inkjet printing, wherein the quantum dot material includes cadmium selenide quantum dots and quantum dot ligands (E)-4-fluorophenethyl 3-(3-hydroxy-4-(methylsulfonyl)phenyl)acrylate coordinated with the quantum dots, wherein the sulfonate group at one end of the quantum dot ligand is coordinated with the dangling bond of zinc on the surface of the quantum dot, and the other end of the quantum dot ligand is an acrylate functional group.

[0078] This embodiment also provides a method for preparing the above quantum dot material, the preparation method comprising the following steps:

[0079] (1) Weigh 1 g of the prepared cadmium selenide quantum dots and disperse them in 20 mL of toluene, and at the same time weigh 0.3643 g of (E)-4-fluorophenethyl 3-(3-hydroxy-4-(methylsulfonyl)phenyl)acrylate and disperse them in 3 mL of n-octanol to form a ligand solution;

[0080] Wherein, the mass ratio of cadmium selenide quantum dots to (E)-4-fluorophenethyl 3-(3-hydroxy-4-(methylsulfonyl)phenyl)acrylate is 1:0.4;

[0081] (2) slowly dripping the ligand solution into a toluene solution containing group II-VI cadmium selenide quantum dots for 10 minutes, and then stirring for 20 minutes for a secondary reaction to obtain a quantum dot material.

[0082] This embodiment also provides a method for preparing quantum dot ink, the preparation method comprising the following steps:

[0083] The quantum dot material and ethyl acetate solution prepared above were centrifuged at 5000 rpm for 3 min, the obtained precipitate was ultrasonically dispersed in 3 g of polypropylene glycol (400) dimethacrylate, and then centrifuged and stirred at 6000 rpm for 3 min to obtain the supernatant, and then 20 μL of 2959 initiator was added thereto to obtain quantum dot ink;

[0084] The volume of the ethyl acetate solution is three times the volume of the quantum dot material, and the mass of the quantum dot material accounts for 25wt.% of the mass of the quantum dot ink.

[0085] This embodiment also provides an application of the quantum dot ink. When the quantum dot ink is applied to inkjet printing, the viscosity range is 20 cp and the surface tension range is 50 dyne / cm.

[0086] Example 4

[0087] The present embodiment provides a quantum dot material for coating or inkjet printing, wherein the quantum dot material includes indium phosphide quantum dots and a quantum dot ligand lecithin coordinated with the quantum dots, wherein one end of the quantum dot ligand is coordinated with the quantum dot, wherein the phosphate group is coordinated with the dangling bond of Zn on the surface of the quantum dot, and the quaternary ammonium group is coordinated with the dangling bond of S on the surface of the quantum dot, and the other end of the quantum dot ligand is an acrylate functional group.

[0088] This embodiment also provides a method for preparing the above quantum dot material, the preparation method comprising the following steps:

[0089] (1) Weigh 1 g of the prepared indium phosphide quantum dots and disperse them in 10 mL of n-hexane, and at the same time weigh 0.3790 g of lecithin and disperse them in 8 mL of n-hexane to form a ligand solution;

[0090] Among them, the mass ratio of indium phosphide quantum dots and lecithin is 1:0.3;

[0091] (2) slowly dripping the ligand solution into a n-hexane solution containing III-V group indium phosphide quantum dots for 10 minutes, and then stirring for 10 minutes to perform a secondary reaction to obtain a quantum dot material.

[0092] This embodiment also provides a method for preparing quantum dot ink, the preparation method comprising the following steps:

[0093] The quantum dot material and ethyl acetate solution prepared above were centrifuged at 5000 rpm for 3 min, the obtained precipitate was ultrasonically dispersed in 3 g of trimethylolpropane formal acrylate, and then centrifuged and stirred at 6000 rpm for 3 min to obtain the supernatant, and then 20 μL of 2959 initiator was added thereto to obtain quantum dot ink;

[0094] The volume of the ethyl acetate solution is three times the volume of the quantum dot material, and the mass of the quantum dot material accounts for 25wt.% of the mass of the quantum dot ink.

[0095] This embodiment also provides an application of the quantum dot ink. When the quantum dot ink is applied to inkjet printing, the viscosity is 18 cp and the surface tension is 30 dyne / cm.

[0096] Figure 1 , Figure 2 , Figure 3 and Figure 4 The fluorescence spectra of the quantum dot materials prepared in Examples 1-4 are shown respectively. It can be seen from the figures that the fluorescence efficiencies are 95%, 96%, 93% and 85% respectively.

[0097] Example 5

[0098] The difference between this embodiment and embodiment 1 is that the molar ratio of the generated FAPbBr3 perovskite quantum dots and 3-[bis[2-(methacryloyloxy)ethyl](methyl)amino]propane-1-sulfonate is 1:0.2.

[0099] The rest of the preparation methods and parameters were the same as those in Example 1.

[0100] Example 6

[0101] The difference between this embodiment and embodiment 1 is that the molar ratio of the generated FAPbBr3 perovskite quantum dots and 3-[bis[2-(methacryloyloxy)ethyl](methyl)amino]propane-1-sulfonate is 1:1.

[0102] The rest of the preparation methods and parameters were the same as those in Example 1.

[0103] Example 7

[0104] The difference between this embodiment and embodiment 1 is that the acrylate functional group at the other end of the quantum dot ligand is replaced by an olefin functional group, that is, the quantum dot ligand is replaced by 1-(3-sulfopropyl)-2-vinylpyridine hydroxide inner salt.

[0105] The rest of the preparation methods and parameters were the same as those in Example 1.

[0106] Example 8

[0107] The difference between this embodiment and embodiment 1 is that the molar ratio of the generated FAPbBr3 perovskite quantum dots and 3-[bis[2-(methacryloyloxy)ethyl](methyl)amino]propane-1-sulfonate is 1:0.125.

[0108] The rest of the preparation methods and parameters were the same as those in Example 1.

[0109] Example 9

[0110] The difference between this embodiment and embodiment 1 is that the molar ratio of the generated FAPbBr3 perovskite quantum dots and 3-[bis[2-(methacryloyloxy)ethyl](methyl)amino]propane-1-sulfonate is 1:3.

[0111] The rest of the preparation methods and parameters were the same as those in Example 1.

[0112] Example 10

[0113] The difference between this embodiment and embodiment 1 is that the mass of the quantum dot material accounts for 5 wt.% of the mass of the quantum dot ink.

[0114] The rest of the preparation methods and parameters were the same as those in Example 1.

[0115] Embodiment 11

[0116] The difference between this embodiment and embodiment 1 is that the mass of the quantum dot material accounts for 50 wt.% of the mass of the quantum dot ink.

[0117] The rest of the preparation methods and parameters were the same as those in Example 1.

[0118] Comparative Example 1

[0119] The difference between this comparative example and Example 1 is that the acrylate functional group at the other end of the quantum dot ligand is replaced by a hydrocarbon group, that is, the quantum dot ligand is replaced by 3-[dimethyl(n-octyl)ammonium]propane-1-sulfonate.

[0120] The rest of the preparation methods and parameters were the same as those in Example 1.

[0121] Comparative Example 2

[0122] The difference between this comparative example and Example 1 is that the added quantum dot ligand is a mixture of 3 mmol oleic acid and 0.5 mmol octylamine.

[0123] Other preparation methods and parameters were consistent with those in Example 1.

[0124] Performance Testing

[0125] The quantum dot ink prepared in the above embodiment and comparative example is applied to inkjet printing to prepare a light-emitting device, and the specific steps include:

[0126] (1) After the inkjet printer is preheated, the quantum dot ink configured as above is loaded into the printer ink cartridge;

[0127] (2) Start printing onto a glass substrate;

[0128] (3) curing the printed substrate under a UV lamp in an inert environment;

[0129] (4) Further, a black bank ink having a polarity greatly different from the ink is coated / evaporated on the entire substrate, covered with another glass substrate, and placed under a UV lamp for curing. Thus, the light-emitting device is completed.

[0130] The luminous efficiency and stability of the above-mentioned light-emitting device are tested.

[0131] The luminous efficiency test conditions are: using the Edinburgh integrated fluorescence spectrometer FS5 with an integrating sphere to test the luminous efficiency of quantum dots.

[0132] The stability test method is as follows:

[0133] (1) Brightness decay rate under blue light radiation conditions: Use blue light with a radiation intensity of 3000 nits to irradiate the quantum dot material with blue light accelerated aging, and record whether the brightness decay amplitude of the quantum dot material in 1000 hours is less than 5% or 10%;

[0134] (2) Brightness decay rate under dry heat storage conditions: The quantum dot material is subjected to dry heat accelerated aging in an oven at 85°C, and the brightness decay amplitude of the quantum dot material after 1000 hours is recorded to be less than 5% or 10%;

[0135] (3) Brightness decay rate under humid heat blue light accelerated aging radiation conditions: At 65°C and 95% RH, the quantum dot composite material is irradiated with blue light of a radiation intensity of 5000 nits, and it is recorded whether the brightness decay amplitude of the quantum dot composite material in 1000 hours is less than 5% or 10%.

[0136] The test results are shown in Table 1.

[0137] Table 1

[0138]

[0139]

[0140] analyze:

[0141] It can be seen from the above table that the present invention uses quantum dot ligands to modify the quantum dots on the surface, so that one end of the quantum dot ligand is connected to the quantum dot ligand, and the other end of the quantum dot ligand can be well dispersed in the ink, thereby effectively improving the luminescence efficiency and stability of the quantum dot material.

[0142] From the data results of Example 1, Example 5-6, and Example 8-9, it can be seen that the ratio within the parameter range protected by the present application can achieve excellent luminous efficiency and anti-aging stability. If the molar ratio of quantum dots to quantum dot ligands is too small, that is, the content of quantum dot ligands is too large, the growth of quantum dots is inhibited, resulting in a small emission peak; if the molar ratio of quantum dots to quantum dot ligands is too large, that is, the content of quantum dot ligands is too small, the quantum dots grow too fast, resulting in low efficiency and a large emission wavelength.

[0143] It can be seen from the data of Example 1 and Examples 3-4 that this solution is applicable to perovskite quantum dots, cadmium selenide quantum dots and indium phosphide quantum dots, and has a wide range of applications.

[0144] It can be seen from the data of Example 1 and Example 7 that the acrylate functional group at the other end of the quantum dot ligand is replaced by an olefin functional group, and this solution is still applicable and still has high luminous efficiency and stability.

[0145] It can be seen from the data results of Examples 1 and 10-11 that if the mass content of the quantum dot material is too low, the color conversion layer will be too thin, resulting in blue light leakage from the color conversion layer; if the mass content of the quantum dot material is too high, the ink viscosity will be too high, resulting in failure to print.

[0146] It can be seen from the data results of Example 1 and Comparative Example 1 that if the acrylate functional group of the quantum dot ligand is replaced by a hydrocarbon group, it cannot play the role of anchoring the quantum dot, resulting in decreased stability.

[0147] It can be seen from Example 1 and Comparative Example 2 that, compared with the quantum dot ligand used in Comparative Example 2, Example 1 has significantly improved luminous efficiency and stability.

[0148] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A quantum dot material for coating or inkjet printing, characterized in that: The quantum dot material includes quantum dots and quantum dot ligands coordinated with the quantum dots, one end of the quantum dot ligand is coordinated with the quantum dots, and the other end of the quantum dot ligand is an acrylate functional group or an olefin functional group; The acrylate functional group or the olefin functional group can be freely dispersed in an organic solvent or bonded to an organic material.

2. The quantum dot material according to claim 1, characterized in that The general chemical formula of the quantum dot ligand includes: X1-R2-SO3 / PO4 / S-R1, X2-R2-N(-R1)-R4-SO3 / PO4 / S-R3 and X3-R2-(R3-)N + At least one of (-R4)-R1-SO3 / PO4 / COO-R3, wherein X1, X2, X3 or X4 is independently an acrylate functional group or an olefin functional group, preferably an acrylate functional group; Preferably, R1, R2, R3 or R4 independently includes any one of a hydrogen group, an alkyl group, an aromatic hydrocarbon group or an ester group, preferably an alkyl group.

3. The quantum dot material according to claim 1 or 2, characterized in that: The quantum dot ligand includes at least one of 3-[bis[2-(methacryloyloxy)ethyl](methyl)amino]propane-1-sulfonate, 1-(3-sulfopropyl)-2-vinylpyridine hydroxide inner salt, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonate, oleyl betaine, (E)-4-fluorophenethyl 3-(3-hydroxy-4-(methylsulfonyl)phenyl)acrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonio]propane-1-sulfonic acid inner salt, 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonate, 3-methylacrylate sulfopropyl ester, 11-phosphonic acid undecyl acrylate and lecithin.

4. The quantum dot material according to claim 1 or 2, characterized in that: The quantum dots include at least one of perovskite quantum dots, II-VI group cadmium selenide quantum dots and III-V group indium phosphide quantum dots.

5. A method for preparing a quantum dot material for coating or inkjet printing according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The quantum dot precursor solution and the quantum dot ligand are mixed, and then heat-treated, and then the precursor material obtained by the heat treatment is mixed with an organic solvent, and a reaction is performed to obtain the quantum dot material for coating or inkjet printing; or, The quantum dot solution and the quantum dot ligand solution are mixed and subjected to a secondary reaction to obtain the quantum dot material for coating or inkjet printing.

6. The preparation method according to claim 5, characterized in that: After the first reaction, the molar ratio of the obtained quantum dots to the quantum dot ligands is 1:(0.2-1); Preferably, the mass ratio of the solute in the quantum dot solution to the solute in the quantum dot ligand solution is 1:(0.2-1); Preferably, the temperature of the heat treatment is 70-120°C; Preferably, the blending time is 20-40 min.

7. A quantum dot ink for coating or inkjet printing, characterized in that: The quantum dot ink comprises the quantum dot material as described in any one of claims 1-4.

8. The quantum dot ink according to claim 7, characterized in that: When the quantum dot ink is used for coating, the coating viscosity ranges from 100 to 1500 cp, and the surface tension ranges from 100 to 1000 dyne / cm; Preferably, when the quantum dot ink is used for inkjet printing, the viscosity ranges from 0.5 to 30 cp and the surface tension ranges from 15 to 55 dyne / cm.

9. A method for preparing the quantum dot ink according to claim 7 or 8, characterized in that: The preparation method comprises the following steps: The quantum dot material, UV glue, initiator and organic solvent are mixed to obtain the quantum dot ink.

10. The preparation method according to claim 9, characterized in that: The mass of the quantum dot material accounts for 5-50wt.% of the mass of the quantum dot ink, preferably 15-30wt.%; Preferably, the UV glue comprises a monomer; Preferably, the monomer comprises at least one of polyethylene glycol (200) dimethacrylate, isooctyl acrylate, isodecyl acrylate, polyethylene glycol (400) dimethacrylate, polyethylene glycol (600) dimethacrylate, tricyclodecane dimethanol methacrylate, trimethylolpropane formal acrylate, triethylene glycol diacrylate glycidyl methacrylate, polypropylene glycol (400) dimethacrylate, isobornyl methacrylate, phenoxyethyl acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate and 1,4-butanediol diacrylate; Preferably, the UV glue further comprises an oligomer; Preferably, the oligomer comprises at least one of aliphatic urethane acrylate, aromatic urethane acrylate, epoxy acrylate and fluorocarbon resin; Preferably, the initiator includes at least one of 1173 initiator, 4265 initiator, 2959 initiator, TPO-L initiator and TPO initiator.

Citation Information

Patent Citations

  • Perovskite ink for ink-jet printing and preparation method of perovskite ink

    CN107474632A

  • Quantum dot ink based on ink-jet printing

    CN109321038A